Hemmende und fördernde Faktoren bei der Durchführung von Studien - die Sicht von Darmkrebszentrumskoordinatorinnen und -koordinatoren = Obstacles and facilitators of conducting studies - the perspective of colorectal cancer centers’coordinators - Kowalski, Christoph; Post, Stefan (Zeitschrift für Gastroenterologie, 2016)
Introduction: Clinical trials and health services research are crucial pillars for improving patient care. This paper examines factors inhibiting and promoting the study activity and the knowledge and use of trial registries (e.g. DRKS, StudyBox) as an opportunity to learn about existing studies. Material and methods: The coordinators of 274 cancer center sites certified according to the requirements of the German Cancer Society were surveyed using a standardized online questionnaire. Data were analyzed using descriptive and bivariate statistics to identify associations with characteristics of the sites (e.g. patient volume, ownership, teaching status). Results: 176 sites participated in the survey (64.2%). The central obstacle to study participa-tion from the centers’ view is the low number of existing studies. General knowledge of the population about studies was considered low. Trial registries are known to almost all respondents, but are rarely used. Discussion: The results of the survey suggest that comprehensive measures are needed to sustainably increase the study activity. These include, for example, better information about studies, for example through appropriate databases, and (industry-independent) research funding. One possible way to sensitize patients for studies could be the comprehensive education of the population about the purpose of studies.
Gesehen am 08.05.2019